The Influence of Madrasah Quality and Brand Image Through Electronic Word of Mouth (E-WoM) on the Decision to Enroll at MI PKP DKI Jakarta - Endang Dwi Mulyani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Electronic Word of Mouth (E-WoM), school quality, and citra merek (brand image) on parents' decisions to enroll their children at MI PKP. The research uses a quantitative approach with a sample of 443 respondents, analyzed using SmartPLS software. The results indicate a significant relationship between the variables E-WoM, school quality, and citra merek (brand image) on parents’ decision-making in selecting MI PKP as an educational institution for their children. E-WOM influences parents’ perceptions of the school’s reputation and quality through online reviews and recommendations. School quality, including aspects such as facilities, curriculum, and teacher competency, plays an essential role in influencing this decision. Citra merek (brand image) also contributes to parents' confidence in the education quality at MI PKP. These findings highlight the importance of strategies to improve service quality and manage the school's image to attract prospective students.